(untitled) (Research, Society and Development, 2021)
In Brazil, about 2.4% of children aged between 0 and 14 years have some type of disability. Cerebral Palsy (CP) is a permanent physical disability with impacts on various organs and systems and, therefore, strategies that enable the full development of children with CP must be planned and implemented. Objective: To review the main characteristics of CP and discuss how the use of interventions such as games and games using inexpensive and easily accessible materials can be useful to stimulate the motor development of children with CP. Methodology: Narrative literature review by consulting the PubMed and SciELO databases, books and documents from organizations, without restriction as to the year of publication, in Portuguese and English. Results and discussion: Changes in the motor development of children with CP include movement, balance, strength and posture. Interventions should occur as early as possible, in different contexts, so that growth and development is facilitated, providing a better prognosis. Among the possibilities, the use of low-cost, recyclable and reusable materials is a strategy that, in addition to motor benefits, brings more playfulness, pleasure and dynamism, favoring greater adherence to activities. Conclusion: The use of inexpensive and easily accessible materials can contribute to the reduction of functional deficits and motor development in children with CP. The construction of games and games with these materials, in addition to making interventions more attractive, can be applied in different environments, including the home and school.